PENGEMBANGAN PENILAIAN PEMBELAJARAN BERBASIS GAMES EDUKASI KAHOOT UNTUK MENINGKATKAN BERPIKIR KRITIS PADA MAPEL IPAS KELAS V SDN 02 JATIREJO KABUPATEN KENDAL - Karimah , Nurani; Yulianto, Sigit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to develop learning assessments using the Kahoot educational game and determine the increase in students' critical thinking skills in the science and science subject of the independent curriculum. The method used in this research is the Borg and gall model. The data obtained was calculated using a Likert scale, normality test, N-gain test to determine the feasibility of the data. The results of the validation test on the material obtained a percentage of 88% and the validation test on the media obtained a percentage of 90%. This can be categorized as